The representation of sex workers in South African media: Danger, morals and human rights - Hunt, Sally; Hubbard, Beatrice (Stellenbosch Papers in Linguistics Plus, 2015)
The ideological construct of gender typically positions women below men, and “others” certain types of women even more, especially those distinguished from idealised femininity by aspects of their sexuality. This paper explores the representation of sex work and sex workers in the South African media in 2009 and 2010, a time during which there was an increase in news coverage of sex work during the 2010 FIFA World Cup. Analysis of the two data sets revealed that sex work is still often perceived as immoral and dangerous, and that sex workers – overwhelmingly represented as women – are criminalised for their actions while client agency is largely obscured, which is in line with previous studies of South African newspapers. However, a strong liberal representation of sex workers was also found in one data set, which advocates the decriminalisation of sex work in the context of human rights. The use of the term “sex work” and its derivatives, rather than “prostitution”, was found to index this progressive stance.